APAKAH INSTITUSI PENTING UNTUK PERTUMBUHAN EKONOMI ? BUKTI EMPIRIS DARI ASEAN - Mu'min, M. Silahul (Bina Ekonomi, 2024)
Institutional quality plays an important role in supporting economic growth through the reduction of transaction costs. This study aims to analyse the effect of institutional quality on economic growth in ASEAN. The data used is a panel of ASEAN countries for the period 2002-2020. Three variables are used as proxies for institutional quality, namely regulatory quality, rule of law, and voice and accountability, while GDP per capita is a proxy for economic growth. Pooled least squares (PLS) was chosen to estimate the relationship between institutional quality and economic growth. The findings of this study show that all institutional quality variables have a significant effect on economic growth in ASEAN. Specifically, rule of law and voice and accountability exert a significantly positive impact on economic growth. However, it is noteworthy that the quality of regulatory frameworks exhibits a significantly negative impact on economic growth in the ASEAN region. The results of this study confirm the institutional role theory which shows that institutions play an important role in promoting economic growth. This study implies that the formulation of regulations or laws should not overlap so that the execution of regulations can run systematically. In addition, it is imperative to foster public participation as a means of government oversight and quality institutions can create a conducive climate for investment.